2003
DOI: 10.1111/j.1444-0594.2003.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Walking speed as a good predictor for maintenance of I‐ADL among the rural community elderly in Japan: A 5‐year follow‐up study from TMIG‐LISA

Abstract: Background  A population‐based prospective cohort study was undertaken to examine the predictors of functional decline in instrumental activities of daily living (I‐ADL) among non‐disabled older Japanese subjects living in a rural community during a five‐year interval from 1992 to 1997. Methods  The subjects consisted of 624 men and women aged from 65–89 years and independent in I‐ADL at baseline, who could be completely followed for five years. Independent variables were various physical factors potentially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 39 publications
5
75
0
Order By: Relevance
“…It has been reported that the walking speed of the older population is associated with performance in standardized tests of physical function 13) . Our results indicate that the walking speed is a good performance measure for predicting the decline of IADL among older Japanese women, similar to previous studies 4,5) . However, for male subjects there was only a weak association between the 5-m walking time and decline in instrumental self-maintenance, and no physical performance test was significantly associated with a subsequent decline in intellectual activities or social roles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that the walking speed of the older population is associated with performance in standardized tests of physical function 13) . Our results indicate that the walking speed is a good performance measure for predicting the decline of IADL among older Japanese women, similar to previous studies 4,5) . However, for male subjects there was only a weak association between the 5-m walking time and decline in instrumental self-maintenance, and no physical performance test was significantly associated with a subsequent decline in intellectual activities or social roles.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, performance measures of lower-extremity function such as walking speed, standing balance and knee-extension strength, are important predictors of subsequent disability in the older population [4][5][6][7][8] . Reduced hand-grip strength is another predictor of disability in older people 9) .…”
Section: Introductionmentioning
confidence: 99%
“…The physical performance test consisted of grip strength and walking speed (Suzuki et al 2003;Studenski et al 2011;Cooper et al 2010). The grip strength of the preferred hand was measured two times using a handheld Smedly-type dynamometer.…”
Section: Subjectsmentioning
confidence: 99%
“…Studies of physical function of the elderly are becoming more important [6][7][8][9] . Regarding the evaluation of the physical function of the elderly, diminished capabilities are commonly encountered in hand-grip strength, gait velocity, timed up-and-go (TUG) at a comfortable speed, and one leg standing time with eyes open.…”
Section: Introductionmentioning
confidence: 99%